2010
DOI: 10.1577/t09-169.1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Upper Temperature Tolerance in June Sucker Larvae: Is the Transition to Utah Lake Temperatures a Recruitment Bottleneck?

Abstract: The June sucker Chasmistes liorus is an endangered adfluvial fish species that is endemic to the Utah Lake basin. This species remains endangered due to a lack of recruitment. Anthropogenic changes to June sucker lotic and lentic habitat has likely led to recruitment failure. Changes to Utah Lake include increased water temperature, increased turbidity, and eutrophic and saline conditions. The remaining spawning habitat for June suckers in the Provo River has experienced flow, temperature, and channelization m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Delta side channels were substantially warmer than other habitats in Utah Lake in which larvae would have drifted during the critical period in June and July. Kindschi et al (2008) found juvenile June Sucker metabolic rate highest at 22 C and larval growth was greatest in the highest temperatures of the treatment, which extended to 27 C (Kappenman et al 2010). Causation for June Sucker survival in the restoration area is speculative given the low number collected, but these results are promising and corroborate evidence of recent natural recruitment within Utah Lake (Wolff et al 2013).…”
Section: Discussionmentioning
confidence: 62%
“…Delta side channels were substantially warmer than other habitats in Utah Lake in which larvae would have drifted during the critical period in June and July. Kindschi et al (2008) found juvenile June Sucker metabolic rate highest at 22 C and larval growth was greatest in the highest temperatures of the treatment, which extended to 27 C (Kappenman et al 2010). Causation for June Sucker survival in the restoration area is speculative given the low number collected, but these results are promising and corroborate evidence of recent natural recruitment within Utah Lake (Wolff et al 2013).…”
Section: Discussionmentioning
confidence: 62%
“…Acclimation temperature (Sylvester, 1975;Schultz and Bertrand, 2011;Zhang and Kieffer, 2014) and latitude (Stewart and Allen, 2014) are two of the main factors that have been shown to significantly affect the upper temperature tolerance of fish. In particular, knowledge of the upper thermal thresholds for fish is useful for predicting physiological responses in thermally dynamic environments (Selong et al, 2001;Kappenman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…
It has been suggested that the mean global surface temperature has increased by 0.7°C over the past 100 years (IPCC 2007, in Lassalle et al, 2010, and it is expected that continued temperature increases could have additional and significant effects on the distribution and survival of many species (Beitinger & Lutterschmidt, 2011;Lassalle et al, 2010). Thermal tolerance data provides information about the potential effects of climate change on fish populations (Beitinger et al, 2000;Deslauriers et al, 2016), and can be useful for predicting physiological responses in thermally dynamic environments (Deslauriers et al, 2016;Kappenman et al, 2010;Tattersall et al, 2012). Various measures of thermal tolerance have been developed; of these, the critical thermal methodology, CTM, (CT max and CT min ) is the most common (Beitinger et al, 2000), and is often used to provide an ecologically and physiologically valuable reference point.
…”
mentioning
confidence: 99%